Sharing Pesan Gizi Seimbang dan Monitoring Pertumbuhan Anak Usia Dini di TK Pertiwi Singodutan II - undari nurkalis; rahayu setyaningsih (Jurnal Pengabdian kepada Masyarakat Indonesia (JPKMI), 2022)
The purpose of this activity is to do community service, especially in the health sector, that can improve the health status of children through monitoring children's growth and sharing balanced nutrition messages in TK Pertiwi Singodutan II. The implementation of this community service activity began with the lecture method and discussion between the Service team and Singodutan II Kindergarten students through sharing messages of balanced nutrition. Then proceed with early detection of growth irregularities through measurements of height, weight, and head circumference. The impact of this community service activity is information on the nutritional status of TK Pertiwi Singodutan II students (based on measurements of height, weight, and head circumference) which can be conveyed to parents as a reference to further improved the health status of early childhood.